GENETIC ANALYSIS FOR GRAIN YIELD AND VARIOUS MORPHOLOGICAL TRAITS IN MAIZE (ZEA MAYS L.) UNDER NORMAL AND WATER STRESS ENVIRONMENTS - M. Hussain; K. N. Shah; A. Ghafoor; T. T. Kiani; T. Mahmood (Journal of Animal and Plant Sciences, 2014)
A genetic analysis study was carried out for various morphological traits in a complete 8 × 8 diallel cross of maize inbred lines under normal irrigation and drought conditions. Estimation of genetic components of variation and graphical presentation deduced that most of the traits like days to pollen shed, anthesis-silking interval, ear height, kernel rows per ear, 100-kernel weight, shelling percentage, grain yield per plant showed over-dominance type of inheritance under both normal and drought conditions unlike leaf rolling which showed partial dominance under normal but over-dominance type of inheritance under drought conditions. It can be inferred that because of over-dominance nature of inheritance of most of the yield related traits, heterosis breeding can be pursued to exploit high yielding hybrids with considerable drought tolerance.
Keywords: additive-dominance model; genetic analysis; Hayman’s diallel approach; Maize